2012
DOI: 10.1097/icl.0b013e31823ff181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contact Lenses on the Ocular Surface in Patients With Keratoconus: Piggyback Versus ClearKone Hybrid Lenses

Abstract: This small sample was not able to demonstrate a difference between the two types of lenses with regard to the variables examined, and further larger trials would be required to determine if differences truly exist or not. However, clinicians may still consider patient comfort and vision in selecting the lens type in patients with keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…They evaluated proinflammatory molecules in tears, stromal keratocyte density, and goblet cell density and found no differences between these types of CL. 39 These finding suggest that Clearkone is at least as safe as piggyback lenses for keratoconus patients.…”
Section: Discussionmentioning
confidence: 69%
“…They evaluated proinflammatory molecules in tears, stromal keratocyte density, and goblet cell density and found no differences between these types of CL. 39 These finding suggest that Clearkone is at least as safe as piggyback lenses for keratoconus patients.…”
Section: Discussionmentioning
confidence: 69%
“…Table 1 One major problem of contact lens wear in generalincluding piggybacked lenses-is hypoxia, neovascularization, and oedema which can be avoided by prescribing lenses with higher oxygen permeability that doesn't induce vascular response [26]. Also, diffuse and localized superficial punctate keratitis and giant papillary conjunctivitis is more prevalent among piggyback contact lens users [24]. These complications can be reduced by good follow up and frequent visits to the clinic.…”
Section: Piggyback System and Other Contact Lenses Optionsmentioning
confidence: 99%
“…Comparison of piggyback contact lens system with ClearKone hybrid lenses-hybrid lens comprises a rigid center of high oxygen permeability and a skirt of soft contact lens material of low oxygen permeability-revealed no significant differences after analyzed bulbar conjunctival impression cytology, tear interleukin-6 (IL-6), tear interleukin-8 (IL-8) levels and confocal microscopic changes of the cornea before and 6 months after wearing contact lenses [24]. Drawbacks of the ClearKone lenses include the limited range of parameters and the difficulty obtaining a successful fit on the highly irregular cornea.…”
Section: Piggyback System and Other Contact Lenses Optionsmentioning
confidence: 99%
“…Contact lenses have some advantages over spectacle corrections (3,4). There are several options such as rigid gas-permeable (RGP) contact lenses (5), hybrid contact lenses (6), piggyback lenses (7) and scleral contact lenses (8).…”
Section: Introductionmentioning
confidence: 99%
“…There are several options such as rigid gas-permeable (RGP) contact lenses (5), hybrid contact lenses (6), piggyback lenses (7) and scleral contact lenses (8). RGP lenses are traditionally first choice because of their success in improving visual acuity (9) RPG lenses improve visual acuity by their refractive power and also by flattening the anterior cornea, increasing the thinnest corneal thickness, and reducing anterior surface high-order aberrations (3,4). Previous studies showed that RGP contact lenses provide a significant improvement in visual acuity compared to spectacles-corrected visual acuity in patients with high corneal astigmatism (10), and keratoconus (11).…”
Section: Introductionmentioning
confidence: 99%